(untitled) (ҚазҰУ Хабаршысы. Биология сериясы, 2017)
Mesenchymal stem cells (MSC) are currently in the focus of attention worldwide as a potential therapeutic tool for osteoarthritis and other types of cartilage damage. Today, a broad range of MSC sources and scaffolds are being tested worldwide to develop a novel cellular therapeutic product. To explore the efficiency of MSC derived from synovial membrane in hyaluronic acid (HA), a rabbit model of osteoarthritis was created by introducing a full-thickness defect onto a cartilage of the medial condyle of rabbit hind limb. Our preliminary results indicate a dramatic improvement in cartilage regeneration under MSC therapy. Also, aiming to optimize culture conditions for MSC, we found optimal concentration of HA to be used for in vitro cell propagation and transplantation.